Safety and efficacy of VRC01 broadly neutralising antibodies in adults with acutely treated HIV (RV397): a phase 2, randomised, double-blind, placebo-controlled trial. Issue 5 (May 2019) - Crowell, Trevor A; Colby, Donn J; Pinyakorn, Suteeraporn; Sacdalan, Carlo; Pagliuzza, Amélie; Intasan, Jintana; Benjapornpong, Khunthalee; Tangnaree, Kamonkan; Chomchey, Nitiya; Kroon, Eugène; de Souza, Mark S; Tovanabutra, Sodsai; et al.
Summary: Background: HIV-1-specific broadly neutralising antibodies such as VRC01 could promote HIV remission by halting viral replication and clearing infected cells. We investigated whether VRC01 could promote sustained viral control off antiretroviral therapy (ART) in adults who initiated ART during acute HIV infection. Methods: We did a randomised, double-blind, placebo-controlled trial at the Thai Red Cross AIDS Research Centre in Bangkok, Thailand. Eligible participants were aged 20–50 years, had initiated ART during acute infection (ie, Fiebig stages I–III), had been taking ART for more than 24 months, had fewer than 50 HIV-1 RNA copies per mL on three consecutive measurements, had more than 400 CD4 cells per μL, had fewer than ten copies of integrated HIV-1 DNA per 10 6 peripheral blood mononuclear cells, and were in generally good health. Eligible participants were randomly assigned (3:1) based on computer-generated lists with a blocking factor of 4 to receive VRC01 (40 mg/kg) or placebo (saline) intravenously every 3 weeks for up to 24 weeks during analytic interruption of ART, followed by continued observation off all therapies. Randomisation was stratified by Fiebig stage (I vs II vs III) at HIV diagnosis. Participants were monitored closely and resumed ART if 1000 or more HIV-1 RNA copies were detected per mL of plasma. The primary outcomes were the frequency of serious adverse events and the proportion of participants with fewer than 50 HIV-1 RNA copies per mL 24 weeks after treatment interruption. Efficacy analyses included all participants who received at least one full dose of study product, and safety analyses included all participants exposed to any study product. The trial was registered withClinicalTrials.gov, numberNCT02664415 . This trial is completed. Findings: Between Aug 8, 2016, and Jan 9, 2017, 19 men were randomly assigned, 14 to the VRC01 group and five to the placebo group. One participant in the VRC01 group received a partial infusion without undergoing treatment interruption. The other 18 participants all received at least one full study infusion and underwent ART interruption. No serious adverse events were reported in either group. Only one participant in the VRC01 group achieved the primary efficacy endpoint of viral suppression 24 weeks after ART interruption. The other 17 restarted ART because of a confirmed recording of 1000 or more HIV-1 RNA copies per mL before 24 weeks. Interpretation: VRC01 monotherapy in individuals who initiated ART during acute HIV infection was well tolerated but did not significantly increase the number of participants with viral suppression 24 weeks after ART interruption. Further development of VRC01 and other immunotherapies for HIV will probably occur as part of combination regimens that include several treatments directed against unique therapeutic targets. Funding: US Department of the Army, US National Institutes of Health, and the Thai Red Cross AIDS Research Centre.